Форми здійснення правотворчого процесу в діяльності Міністерства внутрішніх справ України - Слинько, Д. В. (ХНУВС, 2017)
Досліджено правотворчий процес як різновид юридичного процесу. Вивчено підходи до роз- гляду категорій «нормотворча діяльність» і «відомча нормотворчість» та їх сутності, що скла- лися в юридичній науці. На підставі теоретичного аналізу юридичної літератури визначено, що правотворчий процес у діяльності Міністерства внутрішніх справ України здійснюється у формах відомчого нормотворчого процесу (безпосередній правотворчий процес) та сумісної з іншими вповноваженими суб’єктами правотворчості (опосередкований правотворчий процес). Law-making process as a kind of legal process has been studied. The approaches to the consideration of the categories of “regulatory activity” and “departmental rule-making activity” and their essence within legal science have been studied. On the basis of theoretical analysis of legal literature, the author has determined that the law-making process in the activity of the Ministry of Internal Affairs of Ukraine is carried out in the form of departmental rule-making process (direct law-making process) and common with other authorized subjects of law-making activity (indirect law-making process). The designation of the departmental rule-making process in the activity of the Ministry of Internal Affairs of Ukraine is the modeling of social relations, which, from the standpoint of the state or civil society, are desirable and admissible or necessary and obligatory. The Ministry of Internal Affairs of Ukraine together with other authorized subjects of law-making activity realize the propositions for the improvement of legislation, takes part in the development of the drafts of regulatory acts, the issuing of which falls within the competence of other state agencies or officials. Besides, the Ministry of Internal Affairs of Ukraine within its competence, develops and concludes international treaties and interagency agreements and deals with the interpretation and systematization of regulatory acts.
Forms of the implementation of law-making process in the activities of the Ministry of Internal Affairs of Ukraine
Keywords: правотворчість; нормотворчість; Міністерство внутрішніх справ України; юридичний процес; правотворчий процес; нормотворча діяльність